Cardiometabolic shock: understanding the final turns of the downward spiral - Mathew, Tobin; Kim, Jin Kyung; Gibson, Michael A. (Frontiers in Cardiovascular Medicine, 2025)
Cardiogenic shock (CS) is a state of decreased cardiac output leading to systemic hemodynamic collapse and potential end-organ damage with an elevated risk of mortality. CS represents a heterogenous disease state with varying etiologies, severities, and hemodynamics. Several attempts have been made to characterize CS, including the Society of Cardiovascular Angiography & Interventions shock classification (SCAI), the American Heart Association (AHA) hemodynamic phenotypes, as well as other groups defining shock by underlying clinical factors and pathophysiology. Here, we review cardiometabolic shock, a complex and severe form of CS characterized by severe lactic acidosis and metabolic derangement, systemic inflammation with ischemia/reperfusion injury, persistent vasodilation despite hemodynamic support, and right heart failure, culminating in progressive end-organ failure and a downward spiral of cardiovascular instability. Understanding the components of pathophysiology underlying cardiometabolic shock may help to establish more accurate diagnosis and instituting prompt therapy in the management of this grave cardiac illness. The emerging roles of nitric oxide synthase inhibition, antioxidants, anti-inflammatory agents, proteomics, and artificial intelligence are discussed. Further studies are needed to fully understand cardiometabolic shock and to develop specific effective therapeutic targets.